1993
DOI: 10.1080/15287399309531768
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of radioisotopic beryllium in mice after administration by various routes of injection

Abstract: A 7BeCl2 solution containing 0.5 micrograms Be per mouse was injected subcutaneously, intraperitoneally, intramuscularly, intrathoracically, and intravenously, and distribution was observed for periods up to 1 wk. 7Be was excreted more rapidly following intravenous injection than by the other routes of injection. The amount of Be found in the liver or the spleen was substantial at 1 d after intraperitoneal injection. It increased more in the spleen at 7 d after either intraperitoneal or intrathoracic injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…Distribution of Be in Biological Tissues. The distribution of 10 Be in tissues dosed with 0.5 µg of 9 Be was similar to that measured by Sakaguchi (14). Total body Be recovered from mice by the AMS method and the 7 Be method was also similar (76 ( 5% as compared to the corresponding Sakaguchi results of 63 ( 2%).…”
Section: T H Isupporting
confidence: 79%
See 3 more Smart Citations
“…Distribution of Be in Biological Tissues. The distribution of 10 Be in tissues dosed with 0.5 µg of 9 Be was similar to that measured by Sakaguchi (14). Total body Be recovered from mice by the AMS method and the 7 Be method was also similar (76 ( 5% as compared to the corresponding Sakaguchi results of 63 ( 2%).…”
Section: T H Isupporting
confidence: 79%
“…The 12% intrasample CV of biological samples by AMS is similar to the 9% CV determined in another AMS study for measuring 3 H in biological samples but higher than 2% reported for a new high throughput method for quantifying 14 C by AMS (13,24). In addition, the larger intersample CV as seen in the liver tissue demonstrates the inherent variability that exists between mice in addition to the variability in the sample preparation procedure and the AMS measurements.…”
Section: Quantitation Of Be In Biological Samples By Amssupporting
confidence: 77%
See 2 more Smart Citations
“…An increase in the production of erythroblast cells was observed i n the bone marrow after Be treatment. l O /~ was at 7 d. The percentages of Be retained were at very low levels in the spleen of mice at 1 and 7 d (Sakaguchi et al, 1993). Sakaguchi et al (1 988) previously reported that when 0.5 pg Be was injected into mice subcutaneously, only 0.30h of the administered amount of Be was detected in the blood 30 min after administration, and O .…”
Section: Discussionmentioning
confidence: 91%